Radiating life narratives into engineering education - Omar, Haslina (Asia Pacific Institute of Advanced Research, 2016)
This paper is yet another entry into the exciting field of multidisciplinary studies as it seeks to break walls that have traditionally separated scholars in specialized fields of interest. This study shines literary light onto the area of engineering education as it examines the inclusion of the literary genre of autobiography into the halls of engineering faculties allowing it to serve as a possible generative tool to attract and retain talented men and women in the field of engineering. It offers engineering education a reformulated approach to the reading of life narratives as a means to draw engineering enthusiasts and practitioners into a deeper understanding and a sense of appreciation for their chosen field from literary and psychological perspectives. Psychologists in the area of personality psychology have observed that life stories written by highly generative adults reveal a strong concern for and commitment towards improving and maintaining the quality of life for future generations. This study of life stories of engineers heads a series of studies identifying and examining autobiographies or life narratives written by professional men and women from multi-ethnic backgrounds and how their stories can potentially generate positive outcomes that may include inspiring and encouraging a sense of dedicated commitment and purpose in their chosen fields.